Hyperplasia of the mandibular body: An anomaly in a developmental anomaly - Vaiyapuri Ravi; Saravanan Srinivasan; Mathew Jacob; Priya Kesavan; Rajathi Palani; Sekar Balakrishnan (Wolters Kluwer Medknow Publications, 2013)
Hyperplasias of the mandible are usually seen in relation to the condyle or affecting one half of the mandible, such cases being described as hemimandibular hyperplasia or elongation. This article presents a rare case of hyperplasia of the right body of the mandible. The case being unique in that although being present from childhood did not cause any functional disturbances or any occlusal disharmony characteristically seen in such developmental anomalies. Here, we describe the clinical, radiographic and histopathologic findings that led to the diagnosis hyperplasia of the mandibular body and the treatment rendered to provide the esthetic correction.